Analisis Metode Saw Dalam Merekomendasikan Calon Atlet Bulutangkis PBSI Cabang Kisaran - Dahriansah, Dahriansah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2020)
This study aims to recommend the best Badminton Athlete Candidates in the PBSI branch of the Range based on the criteria determined using decision support system techniques. This multi-criteria decision making technique is based on the theory that each alternative consists of a number of criteria that have values and each criterion has weight that illustrates how important these criteria are with other criteria. The final results obtained from this decision support system will provide an alternative, to recommend the selection of PBSI Badminton Athlete Candidates in the Kisaran branch. The Name of the Best Badminton Athlete According to the Saw Method Calculation is the Mr.A Badminton Candidate Code with a weight of 0.9 Getting First Place.